Tonalt realiseret stød i jysk - Rasmussen, William Alexander (Journal of Language Works - Sprogvidenskabeligt Studentertidsskrift, 2025)
This paper investigates the Danish suprasegmental stød as a falling tone in Jutland. Previous research on the phonetics of stød has mainly focused on Copenhagen Danish, and it has mostly been described as a kind of creaky voice, glottal plosive or laryngalization (Basbøll, 2003; Grønnum, 2005). In dialectal studies of stød, a geographical line through Denmark is described, known as the ‘stød border’. Areas North of the line have stød, and areas south of the line do not, even though some of these areas have tonal accents related to stød. Kyst (2008) is the first to describe stød in the city of Aarhus as a falling tone in certain syllables, but this pattern has not been described in other parts of Jutland prior to this paper. This study finds that in monosyllabic words it mostly occurs on morphophonological closed syllables with long vowels with a few exceptions when the vowel is short around |-d| and |-r| when realized as a diphthong. These exceptions may be a result of individual variation, but possibly they can be explained phonologically. The disyllabic words all have examples of tonal stød no matter what is between the nuclei of the syllables. Keywords: Stød, faldende tone, creaky voice, danske dialekter, jysk, morfofonologi